Evaluation of foot arch in adult women: comparison between five different footprint parameters - Shaliza Mohd Shariff,; Thamilvaani Manaharan,; Asma Ahmad Shariff,; Amir Feisal Merican, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Foot arch determines the shape of the foot, whether it is normal, flat or high. Excessive body weight is known to be the main factor in altering the foot arches. The foot arches of adult women were determined based on five different footprint parameters (Clarke index, Chippaux-Smirak index, Staheli index, Arch index and the Harris-imprint index) and the relationship between Body Mass Index (BMI) and foot arches were studied. A total of 309 adult women from the age of 20 to 60 years were recruited in this study. The shape of participants’ feet were obtained and their left and right foot arches were determined using five different footprint parameters. Body weight and height were measured and BMI was calculated. Paired t-test and one-way ANOVA were applied to perform the statistical analysis. Our analysis showed that two third of the participants have different foot arches between the left and right feet. The Harris-imprint index exhibited the most significant (p=0.004) differences between the left (mean=0.168) and right (mean=1.011) foot arches. Most of the overweight (53%) and obese (15%) participants have normal arches; however the prevalence of flat and high arches is still higher in overweight (flat arch= 51%; high arch= 52% ) and obese (flat arch= 18%; high arch= 12%) compared to other BMI categories. Harris-imprint index was successfully studied as a suitable parameter in determining the left and right foot arches.